Readings on Edmund Husserl’s Logical Investigations
VI, 220 p.
Keywords: I Edmund Husserl's Logische Untersuchungen is, by any standard and also by nearly common consent, a great philosophical work. Within the phenom enological movement, it is generally recognised that the breakthrough to pure phenomenology - not merely to eidetic phenomenology, but also to transcendental phenomenology - was first made in these investiga tions. But in the context of philosophy of logic and also of theory of know ledge in general, these investigations took decisive steps forward. Amongst their major achievements generally recognised are of course: the final death-blow to psychologism as a theory of logic in the Prolegomena, a new conception of analyticity which vastly improves upon Kant's, a theory of meaning which is many-sided in scope and widely ramified in its appli cations, a conception of pure logical grammar that eventually became epoch-making, a powerful restatement of the conception of truth in terms of 'evidence' and a theory of knowledge in terms of the dynamic movement from empty intention to graduated fulfillment. There are many other detailed arguments, counter-arguments, conceptual distinctions and phenomenolo gical descriptions which deserve the utmost attention, examination and assimilation on the part of any serious investigator. With the publication of J. N. Findlay's English translation of the Untersuchungen, it is expected that this work will find its proper place in the curriculum of the graduate programs in philosophy in the English speaking world.